PENYULUHAN PRILAKU HIDUP BERSIH SEHAT DAN GERAKAN MASYARAKAT HIDUP SEHAT PADA LANSIA MENGHADAPI COVID-19 - Etlidawati, Etlidawati; Yulistika, Diyah; Elsanti, Devita (Community Services and Social Work Bulletin, 2021)
COVID-19 is a disease that attacks the respiratory system in humans. This virus has infected millions of people. The elderly is a population group that is quite vulnerable and affected by health and psychological problems in the era of the COVID-19 (new normal) pandemic. One of the government's efforts to protect the elderly from being exposed to this epidemic is to increase the health promotion of the elderly. Elderly by providing counselling. The purpose of the activity is counselling on PHBS and GERMAS (Healthy Living Community Movement) which is part of health promotion in the field of environmental health in breaking the chain of spread of COVID19 and ready to face the new normal. The community can apply healthy living behaviour in the new normal era by applying the 5 M. The Community Service activity method is in collaboration with health cadres Aisyayah Ranting Karangnanas Sokaraja. The series of activities include health checks, namely blood pressure and blood sugar, counselling on healthy living habits and community movements in preventing COVID 19 in the New Normal, namely with 3 M. From the results of the activities, the knowledge of Aisyiyah and the elderly in Karangnanas Village is good knowledge. On average, they can answer about what COVID 19 is, prevention and are able to demonstrate again how to wash hands properly